Fictionalizing the COVID-19 pandemic "instantly". A case study of the German comedy drama Drinnen - Im Internet sind alle gleich - Krauß, Florian (Iluminace, 2023)
Based on interviews with production members and trade magazine articles, the paper discusses how the German comedy drama Drinnen - Im Internet sind alle gleich (2020) dealt with COVID-19 in its production. The series-whose title translates to "Inside - On the Internet All Are Equal"-is obviously about the pandemic: it tells the story of Charlotte, who is planning to quit her job and leave her marriage when she suddenly has to self-isolate and communicate with others only online. Not only Charlotte's fictional life but also the show's real-life production was very much affected by the COVID-19 pandemic. All crew members worked from home, due to Germany's contact restrictions in early 2020. For a fictional production, Drinnen was developed and shot in an extremely fast way-even more so when one considers its public-service context, usually accompanied by complicated bureaucratic structures. The speed and flexibility of the project-based making of Drinnen points to wider changes within its broadcaster, the public-service ZDF - Zweites Deutsches Fernsehen (Second German Television), as well as in German drama production in general. Already before the emergence of COVID-19, attempts had been made to produce serial fiction more quickly, flexibly, and cheaply; under the pandemic, these approaches intensified. While Drinnen is often regarded as an innovative role model in this context, such "instant" drama productions also require critical examination. For the practitioners involved in producing Drinnen, the race to quickly fictionalize the COVID-19 pandemic meant immense pressure.
Keywords: German television; television drama; COVID-19 pandemic; media industry studies; project network